ITRAQ proteomic analysis of N‐acetylmuramic acid mediated anti‐inflammatory capacity in LPS‐induced RAW 264.7 cells. Issue 13 (26th March 2015) - Wu, Zhen; Pan, Daodong; Guo, Yuxing; Zeng, Xiaoqun; Sun, Yangying
<x xml:space="preserve">Abstract</x> Lactobacillus acidophilus probiotic bacteria have lasting beneficial health effects in the gastrointestinal tract, including protecting against pathogens, improving immunomodulation, and producing beneficial bacteria‐derived molecules. In lipopolysaccharide (LPS) induced RAW 264.7 cells treated with peptidoglycan or N‐acetylmuramic acid (NAM) from L. acidophilus, 390 differentially expressed proteins (8.76%) were identified by iTRAQ analysis, 257 (5.77%) of which were upregulated and 133 (2.99%) were downregulated under LPS‐induced conditions. Most of these proteins were grouped into the following inflammation‐related cellular signaling: lysosome pathway, calcium signaling pathway, and Toll‐like receptor (TLR) signaling pathway. Among them, clathrin, SERCA, and interleukin 1 receptor antagonist were differentially expressed to a significant degree in peptidoglycan or NAM pretreated RAW 264.7 cells. Bioinformatics analysis indicated that NAM may mediate an anti‐inflammatory process via a Ca2+‐dependent NF‐κB pathway. These observations reveal new insights into the molecular mechanisms involved in the suppression of LPS‐induced macrophage inflammation by L. acidophilus.